A decoy mutant ACE2 designed to reduce COVID-19. (September 2022) - Maishan, Mazharul; Lim, Diana L.; Zimmerman, Guy A.; Matthay, Michael A.
Abstract : The need for new coronavirus disease 2019 (COVID-19) therapeutic strategies continues, especially as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants emerge. Zhang and colleagues elegantly engineered a mutant angiotensin-converting enzyme 2 (ACE2) that competitively binds SARS-CoV-2 spike protein, reduces viral uptake by human lung cells, and ameliorates SARS-CoV-2-induced lung injury in mice expressing human ACE2.